Stationary-state dynamics of interacting phase oscillators in presence of noise and stochastic resetting - Acharya, Anish; Sarkar, Mrinal; Gupta, Shamik (Physical review, 2025)
We explore the impact of global resetting on Kuramoto-type models of coupled limit-cycle oscillators with distributed frequencies both in absence and presence of noise. The dynamics comprises repeated interruption of the bare dynamics at random times with simultaneous resetting of phases of all the oscillators to a predefined state. To characterize the stationary-state behavior, we develop an analytical framework that spans across different generalizations of the Kuramoto model involving either quenched or annealed disorder or both, and for any choice of the natural frequency distribution. The framework applies to the dynamics both in absence and presence of resetting, and is employed to obtain, in particular, the stationary-state synchronization order parameter of the system, which is a measure of spontaneous ordering among the oscillator phases. A key finding is the pivotal role of correlations in shaping the ordering dynamics under resetting.